Regional governance — ein neues Paradigma der Regionalwissenschaften? - Fürst, Dietrich (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
Regional governance defines weakly institutionalised, network-oriented modes of cooperation between regional actors to achieve common goals of regional development. The scientific discussion on proficiency and coherence of regional governance is still in its infancy. However, there are related theoretical approaches like milieu-theory, learning-regionconception, regulation-school, regime-theory. In the article the peculiarities of regional governance are analysed. Open research questions identified refer to structural elements of governance, issue-selectivity, embeddedness in existing institutions, division of labor with other regional modes of governance, inherent dynamics, legitimization, contribution to regional development and the role of the state.